Manage leafy mistletoes for quality apples - Kumar, Anil; Attri, BL; Kishor, Arun; Ahmed, Nazeer (Indian Horticulture, 2015)
Apple is a major horticultural crop and a remunerative source of income for farmers. Instpite of strong inclination of farmers towards apple, its production is dwindling every year. Besides major diseases and insect/pests, climatic and nutritional factors, parasitic plants have also become a serious problem to sustain/increase apple production in the state. Different species of genus Viscum and other parasitic higher plants have been diagnosed as major flowering parasites of apple with an average incidence of 8-12 per cent. Regular training/pruning of the affected trees with use of Chaubattia paste on the pruned branches accompanied by spray of ethaphon (5%) during dormant stage of the tree is a best possible measure to manage this menace.